C5a receptor blocking in TLR4 mutant C3H/HeJ mouse extensively hampers the liver regeneration process - R. Faiyaz; B. Mallard; N. Leonard; A. Wheatley; Marlini Muhamad (Elsevier, 2024)
Non-Indexed Publication